2005
DOI: 10.1590/s0100-204x2005001000012
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e alterações no fígado e na carcaça de alevinos de jundiá alimentados com dietas com aflatoxinas

Abstract: O objetivo deste trabalho foi avaliar o efeito das aflatoxinas sobre o crescimento de alevinos de jundiá (Rhamdia quelen), e sua deposição no fígado e na carcaça de peixes alimentados com ração com diferentes teores da micotoxina. Foram utilizados 960 alevinos, em dois experimentos, o primeiro com duração de 45 dias e o segundo com 35 dias. As instalações experimentais foram compostas por um sistema termorregulado de recirculação de água. No primeiro experimento, foram avaliados os teores de 41, 90 e 204 ppb d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
2
13
0
11
Order By: Relevance
“…The effect of aflatoxins on the liver and immune system is well known, causing a great deal of damage to the metabolism of proteins, carbohydrates and lipids (Mallmann et al, 1994;Rosmaninho et al, 2001;Bennett;Klich, 2003). The fishes receiving aflatoxin become sensitive to stress due to environmental and microbial factors (Rosmaninho et al, 2001;Lopes et al, 2005). It is believed that the same may have occurred in our study, with reduced parameters of apparent feed conversion and total length.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The effect of aflatoxins on the liver and immune system is well known, causing a great deal of damage to the metabolism of proteins, carbohydrates and lipids (Mallmann et al, 1994;Rosmaninho et al, 2001;Bennett;Klich, 2003). The fishes receiving aflatoxin become sensitive to stress due to environmental and microbial factors (Rosmaninho et al, 2001;Lopes et al, 2005). It is believed that the same may have occurred in our study, with reduced parameters of apparent feed conversion and total length.…”
Section: Discussionsupporting
confidence: 72%
“…Arana et al (2002) showed that the trout genotype can significantly affect the effect of aflatoxins on growth parameters and weight gain. The catfish is a resistant fish (Jantrarotai;Lovell, 1991), which was also confirmed by Lopes et al (2005) after evaluating the effect of aflatoxins on catfish. This indicates the importance of the impact of the species and intrinsic genetic components on the effects caused by micotoxins on fish, and this may explain some of the results described in this study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Além disso, observou-se também diminuição no ganho com o aumento dos níveis de adsorvente na dieta. Valores semelhantes também foram encontrados por Lopes et al (2005), de 0,23 g de ganho de peso médio diário, com ração controle para alevinos de jundiá em 45 dias experimentais. De certa forma, o peso corporal dos alevinos de jundiá foi proporcional ao crescimento (padrão e total), pois houve diferença significativa no fator de condição corporal, de modo que a ração controle, sem adsorvente, resultou em índice de 0,82, e, com a inclusão de aflatoxina, o fator de condição corporal baixou até valores de 0,72 (Tabela 3).…”
Section: Resultsunclassified
“…Diversos estudos comprovaram também que a bentonita sódica é um ótimo adsorvente para aflatoxinas em aves, do mesmo modo que as ASSCA (Mallmann et al, 2007).…”
Section: Introductionunclassified